2016
DOI: 10.5772/60692
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Science and Technology - Progress in Physical States and Chemical Reactions

Abstract: Non-thermal plasma technology is one of those techniques that suffer relatively little from diffusion limits, slow kinetics, and complex geometries compared to more traditional liquid-based chemical surface modification techniques. Combined with a lack of solvents, preservation of the bulk properties, and fast treatment times; it is a well-liked technique for the treatment of materials for biomedical applications. In this book chapter, a review will be given on what the scientific community determined to be es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…In a 2016 review, [8] Vanraes et al reported on yet another recently investigated group of configurations, so called "remotely generated plasmas", in which the plasma is generated outside of the liquid phase and its radical products are bubbled into the solution. The principle is similar to ozonation, with the important difference, however, that the bubbled gas also contains other reactive species, such as H 2 O 2 and OH radicals.…”
mentioning
confidence: 99%
“…In a 2016 review, [8] Vanraes et al reported on yet another recently investigated group of configurations, so called "remotely generated plasmas", in which the plasma is generated outside of the liquid phase and its radical products are bubbled into the solution. The principle is similar to ozonation, with the important difference, however, that the bubbled gas also contains other reactive species, such as H 2 O 2 and OH radicals.…”
mentioning
confidence: 99%
“…Versatility and ease of measurement make emission spectroscopy attractive, but interpretation of the data can often be challenging. Emission measurements collect light from a specified region along the main axis of the collection optics, and collection efficiency varies with spatial location in the plasma [7,17]. Thus the collected spectrum is the convolution of many weighted spectra from the collection volume.…”
Section: Introductionmentioning
confidence: 99%